Lethal Violence and Peripheral Youth Extermination in Brazil Amazon Region - Deluchey, Jean-François Yves; Santos, Amanda Laysi Pimentel Dos (International Journal of Criminology and Sociology, 2018)
This work aims to discuss the homicide problem in the Brazilian Amazon region, based on the analysis of data collected by DATASUS, Sangari and Ipea Institute on homicides in Brazil, which were systematized within the framework of the “Amazonias: Knowledge and Changes” project, and by interviews analysis carried out with relatives of victims of the region. Based on these studies, which point out that the main victims of this type of violence are youth from the peripheries and using the notion of sociodiversity, we try to understand how violence against this youth maintained relation with neoliberalism set of governmental practices, as described by Michel Foucault in The Birth of Biopolitics. In this way, we think possible to provide a synthesis of the major problems of lethal violence and extermination of peripheral youth in the Amazon Region.